Impact of Bolivian paleolake evaporation on the δ18O of the Andean glaciers during the last deglaciation (18.5–11.7 ka): diatom-inferred δ18O values and hydro-isotopic modeling. (15th July 2015) - Quesada, Benjamin; Sylvestre, Florence; Vimeux, Françoise; Black, Jessica; Paillès, Christine; Sonzogni, Corinne; Alexandre, Anne; Blard, Pierre-Henri; Tonetto, Alain; Mazur, Jean-Charles; Bruneton, Hélène
Abstract: During the last deglaciation, the Bolivian Altiplano (15–23°S, 66–70°W) was occupied by paleolake Tauca covering, at least, ∼51, 000 km 2 at its maximum highstand between 16.5 and 15 ka. Twenty-five hundred years later, after a massive regression, a new transgressive phase, produced paleolake Coipasa, smaller than Tauca and restricted to the southern part of the basin. These paleolakes were overlooked at the west by the Sajama ice cap. The latter provides a continuous record of the oxygen isotopic composition of paleo-precipitation for the last 25 ka. Contemporaneously to the end of paleolake Tauca, around 14.3 ka, the Sajama ice cap recorded a significant increase in ice oxygen isotopic composition (δ 18 Oice ). This paper examines to what extent the disappearance of Lake Tauca contributed to precipitation on the Sajama summit and this specific isotopic variation. The water δ 18 O values of paleolakes Tauca and Coipasa (δ 18 Olake ) were quantitatively reconstructed from 18.5 to 11.7 ka based on diatom isotopic composition (δ 18 Odiatoms ) and ostracod isotopic composition (δ 18 Ocarbonates ) retrieved in lacustrine sediments. At a centennial time scale, a strong trend appears: abrupt decreases of δ 18 Olake during lake fillings are immediately followed by abrupt increases of δ 18 Olake during lake level stable phases. The highest variation occurred at ∼15.8 ka with a δ 18 Olake decrease of about ∼10‰, concomitant with the Lake Tauca highstand, followed ∼400 years later by a 7‰ increase in δ 18 Olake . A simple hydro-isotopic modeling approach reproduces consistently this rapid "decrease–increase" feature. Moreover, it suggests that this unexpected re-increase in δ 18 Olake after filling phases can be partly explained by an equilibration of isotopic fluxes during the lake steady-state. Based on isotopic calculations during lake evaporation and a simple water stable isotopes balance between potential moisture sources at Sajama (advection versus lake evaporation), we show that total or partial evaporation (from 5 to 60%) of paleolake Tauca during its major regression phase at 14.3 ka could explain the pronounced isotopic excursion at Sajama ice cap. These results suggest that perturbations of the local hydrological cycle in lacustrine areas may substantially affect the paleoclimatic interpretation of the near-by isotopic signals (e.g. ice core or speleothems). Highlights: We quantify δ 18 O of Bolivian paleolakes (18.5–11.7 ka) using diatoms and ostracods. Abrupt decrease of δ 18 Olake during lake fillings is followed by δ 18 Olake increases. Hydro-isotopic modeling approach is performed to explain the δ 18 Olake signal. 5–60% of lake evaporation could have explained an isotopic excursion at Sajama. Local hydrological processes could affect regional precipitation-proxy records.